IMPLEMENTASI PROGRAM PENERIMAAN BANTUAN SEMBAKO DI DESA GENTAWANGI KECAMATAN JATILAWANG KABUPATEN BANYUMAS - Respitaningsih, Apriani; Suryoto, Suryoto (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2024)
The formulation of the problem proposed is: How to Implement the Basic Food Assistance Receipt Program in Gentawangi Village, Jatilawang District, Banyumas Regency. The aim of this research is to find out how the Basic Food Assistance Receipt Program is implemented in Gentawangi Village, Jatilawang District, Banyumas Regency. The data analysis technique used in this research is descriptive qualitative analysis with an interactive model. The method for determining informants used the Purposive Sampling technique, with the informants being employees of the Basic Food Assistance Implementing Cadre (1 person), the Head of the Service Section (1 person), and the community receiving basic food assistance in Gentawangi Village (5 people), a total of 7 informants. Based on the discussion of the previous research results, several conclusions can be drawn that: The Basic Food Program is government assistance aimed at helping people face difficulties in meeting their daily needs for people in the poor category. One of them is the basic food assistance program, which is a social food assistance program held by the City Government in accordance with instructions from the Minister of Home Affairs to overcome the impact on society. The target of this program is of course the less fortunate. The Communication Dimension or Target Accuracy of the Basic Food Assistance Receiving Program is measured from the target group dimension by looking at the communication aspect of target accuracy and the socialization process which can be concluded that the target accuracy process has been determined, namely that the poor are included in the DTKS. Improving the Quality of Human Resources (HR) is a Program for Receiving Basic Food Assistance which means that improving the quality of HR/employee training is quite clear. Basic food needs and the budget source comes from the Social Service/APBN. The budget is very sufficient for the residents of Gentawangi Village who receive basic food assistance from the Social Service.Implementation Attitude is an activity which certainly cannot be separated from the implementation attitude, whether in the form of support or otherwise. One of the implementation attitudes is support from the government as well as support from the village and community